Suppose for polynomials f, g in $\mathbb{Q}[X]$ it holds that

$$\gcd(f(X),g(X))=d(X)$$

What we also want to now prove is that for $a \in \mathbb{Q}$: $$\gcd(f(X+a),g(X+a))=d(X+a)$$

So the question is asking that if we replace $X$ by $X+a$, the new gcd is the old one evaluated at $X+a$. I was thinking that we can always write: $$ \alpha(X) f(X)+ \beta(X) G(X) =d(X)$$ For polynomials $\alpha$, $\beta$, but I don't see how I could use this. If I would just treat $d(X)$ as a function now and shift by $a$ to the left, the proof would immediately follow, but this feels a bit like cheating, is this statement valid?

I would then finish like:

If we now treat $d(X)$ as a function, we shift the function $a$ to the left and get: $$d(X+a)=\alpha(X+a) f(X+a)+ \beta(X+a) g(X+a) .$$ Since we still have $\alpha(X+a), \beta(X+a) \in \mathbb{Q}[X]$ this statement is equivalent to: $$\gcd(f(X+a),g(X+a))=d(X+a) .$$ as desired $\square$.

  • 1
    Why do you think a valid inference is "cheating"? – Bill Dubuque Oct 11 at 15:35
  • Because I didn't really know why I was allowed to do it ;) – Wesley Strik Oct 11 at 16:29
up vote 1 down vote accepted

Hint $ $ shifts $\,f\mapsto \bar f$ are automorphisms so preserve divisibility $\ cd=a\iff \bar c \bar d = \bar a,\,$ so gcds

$$ c\mid (a,b)\iff c\mid a,b\iff \bar c\mid \bar a,\bar b\iff \bar c\mid (\bar a ,\bar b)$$

I think one problem might be $$p(x+a)f(x+a) + q(x+a)g(x+a) = d(x+a)$$ does not imply $$d(x+a)=\gcd(f(x+a),g(x+a)),$$ only that their $\gcd$ divides $d(x+a)$.

For example you can multiply arbitrarily large degree $k(x)$ to $p(x+a), q(x+a)$ and $d(x+a)$.

Perhaps arguing along with degree of $d(x), d(x+a)$ can work. I guess this also means $a$ must be defined as not a root.

But if $a$ is not a root perhaps another way is: we can find $p(x),q(x)$ such that $$ p(x)(f(x)/d(x)) + q(x)(g(x)/d(x)) = 1 $$ Therefore $$ p(x+a)(f(x+a)/d(x+a)) + q(x+a)(g(x+a)/d(x+a)) = 1 $$ This time round we can say something concrete about their $\gcd$: $$ D(x) = \gcd(f(x+a)/d(x+a),g(x+a)/d(x+a)) = 1, $$ as otherwise there is some non-constant polynomial $D(x)$ that divides $1$.

Therefore $$ \gcd(f(x+a),g(x+a)) = d(x+a) $$

  • Why does $p(x)(f(x)/d(x)) + q(x)(g(x)/d(x)) = 1 $ imply that $ p(x+a)(f(x+a)/d(x+a)) + q(x+a)(g(x+a)/d(x+a)) = 1$ ? – Wesley Strik Oct 11 at 12:59
  • Since the relations holds for all X, it must also hold for $X+a$? – Wesley Strik Oct 11 at 13:33
  • @WesleyGroupshaveFeelingsToo Right, it really should have been written as $$f(x)/d(x) = u(x) \in \mathbb Q[x]$$ and similarly $v(x)$ for $g(x)/d(x)$. Then the change of variables hold and we can work with $u(x+a), v(x+a)$ first until $\gcd(u(x+a),v(x+a))=1$. Then $$\gcd(u(x+a)d(x+a),v(x+a)d(x+a)) = d(x+a)$$ and we can plug back $f,g$. Then translate $x+a$ back to $x$. – Yong Hao Ng Oct 11 at 14:03

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.